Encoding Smart Microjoints for Microcrawlers with Enhanced Locomotion. (18th February 2020) - Chen, Qianying; Lv, Pengyu; Huang, Tian-Yun; Huang, Jianyong; Duan, Huiling
Abstract : Usually, it is indispensable for traditional functional robots to use flexible joints that integrate sophisticated machinery and control systems to achieve precise operability and efficient mobility. At the microscale, however, the conventional design of functional joints is generally not suitable due to the limitation of the manufacturing process on such a tiny size. Herein, a strategy for the design of smart microjoints (SMJs) that undergo controllable active deformation by triggering a size‐dependent layer‐by‐layer sequential swelling effect on SMJs in response to external stimuli is developed. The optimal encoding of SMJs that enables microcrawlers to achieve superior crawling speed (0.15 body length s −1 ) and efficiency (1.1 body length per step), as well as controllable locomotion, is demonstrated, e.g., migration along/against the stimuli source or along a preplanned path. A path toward constructing soft actuators/robots at the microscale with high adaptability and controllability for broad engineering applications is offered. Abstract : The concept of smart microjoints (SMJs) is proposed and designed by the computer‐aided finite‐element method, which can achieve controllable active deformation in response to external stimuli. Bionic microcrawlers are developed by encoding SMJs, which can realize a superior crawling speed, efficiency, and programmable locomotion. Herein, a novel strategy for structural designs, functional assembly, and optimizations of soft microrobots is presented.